Factores críticos en la sostenibilidad de los emprendimientos en el cantón Echeandía, provincia Bolívar - Naranjo Maliza, Katerine Noemi (2019)
The present work Critical Factors in the Sustainability of Entrepreneurships in the Echeandía canton, Bolívar Province, year 2019, has been prepared with the purpose of identifying those factors, since it was verified that their sustainability in the mentioned canton has decreased, Currently there are people who close and open businesses, which causes instability in economic growth. It is known as critical factors to the elements that affect business in one way or another causing the closure of ventures, so it is important to know them, since their presence has generated fear and the absence to undertake. The results obtained through the application of the survey are that as critical factors for the creation and sustainability of enterprises is financial support, government policies and parttime dedication to entrepreneurship. While key factors for sustainability of the enterprises are considered financing, entrepreneurship, management and negotiation expertise, full time dedication to entrepreneurship, age of the entrepreneur and social status. Therefore, a proposal was made that minimizes the impact of critical factors on business sustainability entitled Strengthening of enterprises in the Echeandía canton, Bolívar province, period 2019-2021, which will have a social and economic impact, since commercial activity will be increased, dynamisation of the unstable economy and strengthening of the commercial structure of the business.